Analisis Persepsi Dan Partisipasi Masyarakat Terhadap Pengelolaan Mangrove Berkelanjutan - Serkadifa, Yetty S.; Matinahoru, J. M.; Pattimahu, D. V. (Universitas Pattimura, 2019)
Mangrove forests produce environmental services is a very important role for the community around it as well as the community outside of the mangrove forest, adanya forest management programs implemented by the Government of the mangrove in the preserve sustainable mangrove forests in the town of Sorong. This is evidenced by a factor of education and income are very berpegaruh towards the level of participation, so that the involvement of the respondent are very helpful in the conservation of mangrove forests. Based on the analysis of the Chi square obtained the results that count amounted to 36.43 X2 is greater than X2 table 28.29 at 0.01 significant degree it can be concluded that H0 is rejected and the Ha are received. This means there is a real relationship between the level of public participation by education level of the respondents. Participation rates based on income, obtained the results that count of 31.35 X2 is greater than X2 table 28.29 on significant value of 0.01 degrees degrees of freedom 16. It can be concluded that H0 is rejected and the Ha are received.